2002
DOI: 10.1002/clc.4960250905
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic subclinical primary alterations in marfan syndrome and marfan‐related disorders

Abstract: SummaryBackground: The extracellular matrix tissue of the myocardium importantly contributes to left ventricular (LV) performance. Inherited connective tissue disorders related to the FBN1 gene could involve cardiac interstitium resulting in functional abnormalities.Hypothesis: To disclose a primary involvement of myocardium, LV function was studied in 28 patients affected by Marfan syndrome or Marfan-related disorders: 20 Marfan and 8 MASS (Mitral valve prolapse, Myopia, Aortic dilatation, Skeletal involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
(38 reference statements)
0
14
0
1
Order By: Relevance
“…A first study conducted with MRI and echocardiography in children demonstrated impaired LV diastolic function with an increased deceleration time and isovolumic relaxation time ascribed to weakened elastic recoil [8]. A subsequent echocardiographic study showed an unusual pattern of transmitral diastolic flow in which a decreased ventricular compliance (decreased deceleration time) and reduced myocardial relaxation (increased isovolumic relaxation time) coexist [9]. Our study demonstrated a prolongation of the early filling phase of the left ventricle.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A first study conducted with MRI and echocardiography in children demonstrated impaired LV diastolic function with an increased deceleration time and isovolumic relaxation time ascribed to weakened elastic recoil [8]. A subsequent echocardiographic study showed an unusual pattern of transmitral diastolic flow in which a decreased ventricular compliance (decreased deceleration time) and reduced myocardial relaxation (increased isovolumic relaxation time) coexist [9]. Our study demonstrated a prolongation of the early filling phase of the left ventricle.…”
Section: Discussionmentioning
confidence: 58%
“…Impairment of left ventricular (LV) function in MFS may occur as a consequence of significant valvular disease, but there is also recent evidence for impaired LV function, in the absence of valvular heart disease, as expressed by increased LV diameters in a small subset of patients [6,7]. Similarly, there are indications that left ventricular diastolic function is impaired in MFS, but the available data are scarce [8,9].…”
Section: Introductionmentioning
confidence: 94%
“…9 Tissue Doppler imaging has not been used previously to scrutinize LV performance in MFS, and diastolic Doppler parameters were obtained only in children 15 and in a heterogeneous group of younger adults with MFS or mitral aortic skin skeletal (MASS) phenotype. 17 These Doppler studies, however, corroborate a normal LV ejection fraction with prolonged IVRT 17 and DT 15 and document presence of impaired LV relaxation in MFS. 18 Our TDI studies further establish an impaired early diastolic function and document reduced systolic contraction velocities.…”
Section: Discussionmentioning
confidence: 83%
“…Die Untersuchung von beschwerdefreien, suspekten Familienmitgliedern kann, bei autosomal-dominantem Erbgang mit großer Penetranz, in gleicher Weise empfohlen werden [10,36,56,60]. Harmlos erscheinende "Spinnenfinger", ein asthenischer Habitus und andere Symptome am Bewegungsapparat können hierbei als Wegweiser für lebensrettende Untersuchungsschritte dienen.…”
Section: Klinik Der Begleitmanifestationenunclassified